2007
DOI: 10.1152/ajpregu.00069.2007
|View full text |Cite
|
Sign up to set email alerts
|

Delayed angiogenesis and VEGF production in CCR2−/− mice during impaired skeletal muscle regeneration

Abstract: The regulation of vascular endothelial growth factor (VEGF) levels and angiogenic events during skeletal muscle regeneration remains largely unknown. This study examined angiogenesis, VEGF levels, and muscle regeneration after cardiotoxin (CT)-induced injury in mice lacking the CC chemokine receptor 2 (CCR2). Muscle regeneration was significantly decreased in CCR2−/− mice as was the early accumulation of macrophages after injury. In both mouse strains, tissue VEGF was similar at baseline (no injections) and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
157
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(181 citation statements)
references
References 47 publications
10
157
1
Order By: Relevance
“…Instead of the stereotypic inflammatory response in acutely injured muscle, CTX-injected muscles in CCR2-null mutant mice showed a greatly reduced invasion of macrophages into the injury site, while neutrophil numbers were elevated for a prolonged period (80). In addition, injured muscles in CCR2 mutants showed persistent necrosis of muscle fibers and a slowed growth of fiber diameter at the injury site.…”
Section: Do Neutrophil-derived or M1 Macrophage-derived Molecules Modmentioning
confidence: 87%
See 1 more Smart Citation
“…Instead of the stereotypic inflammatory response in acutely injured muscle, CTX-injected muscles in CCR2-null mutant mice showed a greatly reduced invasion of macrophages into the injury site, while neutrophil numbers were elevated for a prolonged period (80). In addition, injured muscles in CCR2 mutants showed persistent necrosis of muscle fibers and a slowed growth of fiber diameter at the injury site.…”
Section: Do Neutrophil-derived or M1 Macrophage-derived Molecules Modmentioning
confidence: 87%
“…As in other tissues, Ly6Cϩ/F4/80-neutrophils are the first responders and begin to appear at elevated numbers within 2 h of muscle damage, typically peaking in concentration between 6 and 24 h postinjury and then rapidly declining in numbers. Following the onset of neutrophil invasion, phagocytic macrophages begin to invade, reaching significantly elevated concentrations at about 24 h postinjury and continue to increase in numbers until about 2 days postinjury, when their numbers begin to decline sharply (8,16,26,80,98,109,117). Their invasion precedes the elevation of a population of nonphagocytic macrophages that reaches peak concentrations in the muscle at about 4 days postinjury but remains significantly elevated for many days (Fig.…”
Section: Changes In Myeloid Cell Phenotype In Muscle Following Injurymentioning
confidence: 96%
“…VEGF is able to enhance myoblast migration in vitro and prevent apoptosis of myoblasts in cell culture and in skeletal muscle following ischemia (42). In addition, impaired muscle regeneration was observed in mice during delayed angiogenesis and low-level VEGF production (43). Maximal capillary density postinjury was observed concomitant with the restoration of tissue VEGF (43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, impaired muscle regeneration was observed in mice during delayed angiogenesis and low-level VEGF production (43). Maximal capillary density postinjury was observed concomitant with the restoration of tissue VEGF (43). This might indicate that growing, regenerating muscle fibers have an increased need for nutrient delivery, which can be accomplished by increased capillary density.…”
Section: Discussionmentioning
confidence: 99%
“…26 Inversely, in mice exhibiting delay and impairment of muscle regeneration (CCR2 -/-mice), VEGF level is decreased until day 21, time of restoration of maximal capillary density. 27 The authors showed that maximal capillary density developed concurrent with the restoration of tissue VEGF, and observed an inverse relationship between the size of regenerated muscle fibres and the number of capillaries. 27 These studies indicates the existence of VEGF-dependent mechanisms at work in the dynamic processes of capillary formation and muscle regeneration.…”
Section: Interplays Between Ecs and Myogenic Cells 44mentioning
confidence: 99%